2019
DOI: 10.3390/ani9090667
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Hha1 Calpastatin Gene Polymorphism, Growth Performance, and Meat Characteristics of Awassi Sheep

Abstract: Simple SummaryThe Awassi sheep is a very important breed, and using molecular selection to enhance meat production is important. Following genotyping of Awassi sheep housed at two different research stations in Jordan, three genotypes were identified for the calpastatin Hha1 gene. Following a fattening trial, the polymorphic calpastatin gene affected final (marketing) body weight and longissimus muscle width. Hha1 restriction sites found in Calpastatin gene can be used for molecular marker-assisted selection i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 16 publications
1
17
0
3
Order By: Relevance
“…In this study, two CAST genotypes were detected with frequencies of 0.65 and 0.35 for MN and NN genotype, respectively. These results are in agreement with previously reported data in different breeds of sheep [11]. In this study, lambs with heterozygous CAST gene were found to have significantly higher percentages of neutrophils and lower percentages of lymphocytes.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In this study, two CAST genotypes were detected with frequencies of 0.65 and 0.35 for MN and NN genotype, respectively. These results are in agreement with previously reported data in different breeds of sheep [11]. In this study, lambs with heterozygous CAST gene were found to have significantly higher percentages of neutrophils and lower percentages of lymphocytes.…”
Section: Discussionsupporting
confidence: 94%
“…Whether this difference has a significant effect on disease resistance in MN lambs requires further investigation. Previous research in Awassi sheep has reported superior performance of MN CAST genotype [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Awassi (AW) is a multipurpose fat-tailed sheep breed, well adapted to harsh environmental conditions, and the predominant sheep breed in Jordan, Lebanon, and the Middle East. The AW sheep breed suffers from inferior carcass merit and poor leg muscling [1]. With consumers requiring meat with more lean and less fat without compromising juiciness and flavor [2], heavier carcasses could be advantageous for producers by providing higher profit from meat sales and for consumers by supplying more mature meat with better quality [3].…”
Section: Introductionmentioning
confidence: 99%
“…The allelic frequencies of alleles M and N were 0.81 and 0.19, Determination of the Polymorphism of the Booroola Fecundity B, Callipyge and Calpastatin Genes in Assaf Sheep Breed... respectively (Table 4). These results show that the desired MN genotype which is associated with satisfactory weight gain in lambs and meat tenderness after slaughter Palmer et al, 1998) (Jawasreh et al, 2017).…”
Section: Resultsmentioning
confidence: 65%